The ultramicropore biochar derived from waste distiller’s grains for wet-process phosphoric acid purification: Removal performance and mechanisms of Cr(VI) - Su, Kai; Hu, Guotao; Zhao, Tianxiang; Dong, Huinan; Yang, Yi; Pan, Hongyan; Lin, Qian (Chemosphere (Oxford), 2024)
Solid waste and heavy metal pollution are long-term and challenging subjects in the field of environmental engineering. In this study, we propose a sustainable approach to “treating waste with waste” by utilizing the ultramicropore biochar derived from solid waste distiller’s grains as a means to remove Cr(VI) from simulated wastewater and wet phosphoric acid. The biochar prepared in this research exhibit extremely high specific surface areas (up to 2973 m2/g) and a well-developed pore structure, resulting in a maximum Cr(VI) adsorption capacity of 426.0 mg/g and over 99% removal efficiency of Cr(VI). Furthermore, the adsorbent can be reused for up to eight cycles without significant reduction in its Cr(VI) adsorption performance. Mechanistic investigations suggest that the exceptional Cr(VI) adsorption capacity can be attributed to the synergistic effect of electrostatic interaction and reduction adsorption. This study offers an alternative approach for the resource utilization of solid waste distiller’s grains, and the prepared biochar holds promise for the removal of Cr(VI) from wastewater and wet-process phosphoric acid. [Display omitted] •Biochar derived from distiller’s grains is used for removal Cr(VI).•Biochar exhibits a remarkably high specific surface area.•A maximum adsorption capacity for Cr(VI) of 426.0 mg/g is acquired.•A combined physical and chemical interaction for Cr(VI) removal is proposed.